MORPHOLOGICAL ANALYSIS OF Bruguiera gymnorrhiza AT TUNDA ISLAND, BANTEN, IMPLICATIONS FOR MANGROVE ECOSYSTEM CONSERVATION - Lydia Ayu Utami; Lisna Lidiawati; Rangga Saputra; Putra Sasi Ramadhan; Yudha Alkindi; Ilham Bintang Alfirdausy; Moch. Saad (Jurnal Penelitian Perikanan Laut (Albacore), 2026)
Mangrove ecosystems play an important role as habitats for biota, natural coastal buffers, and carbon sinks. This study examines the morphological and morphometric characteristics of Bruguiera gymnorrhiza at Tunda Island, Serang, Banten, to understand species adaptation to dynamic tidal conditions and the effects of plastic waste accumulation on vegetation growth. Field observations were conducted at six sampling sites using a line transect–quadrat method. Data included measurements of stems, leaves, flowers, and fruits, as well as observations of stomata and cambium. The results showed tree heights of 7–15 m, diameters of 15–123 cm, leaf lengths of 5–21.5 cm, flower lengths of 2.8–5 cm, and fruit lengths of 6–16.3 cm. Anomocytic stomata and active cambium indicate adaptation to high salinity and muddy environments. Differences between the eastern and southern parts of the island, related to hydrodynamics, substrate, and plastic pollution, resulted in higher Bruguiera gymnorrhiza density in the east. The Shannon–Wiener diversity index was low (H’ east = 0.795; south = 0.3466), indicating species dominance. These findings support mangrove management and conservation efforts, particularly through plastic waste reduction and salinity monitoring. Key words: coastline, conservation, mangrove ecosystem, Tunda Island